Analisis Strategi Marketing PT Grand Sahid Jaya Hotel Jakarta - , Indriasari Herdianti, Dr. John Suprihanto, MIM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Based on Sales and Marketing reports, the occupancy of Grand Sahid Jaya in April 2011 decreased by 5,90 percent compared with April 2010. While according to BPS data thereâs an increased number of foreign tourist. Compared with competitors such as intercontinental, Sari Pan, Le Meredien and Sultan, The occupancy of Grand Sahid Jaya is lower. The purpose of this study is to analyze and evaluate marketing strategies of Grand Sahid Jaya from the external and internal environment of the company. The technique which used in this study are literature studies, interview and documentation studies. Type of study is qualitative descriptive. The method of analysis that been used is SWOT analysis with an appropriate weighting given to the characters of the hotel business. The result on IFAS table show Sahid Jaya have 1.195 and the result on EFAS show 0.8 which means this positive value indicates that the Hotel still have the power that can be used to cover up weaknesses